The landscapes of tourism space - Bogdan Włodarczyk (Tourism, 2009)
The author attempts to define the term ‘tourism landscape’. It is treated as an important attribute of tourism space therefore, apart from its definition, the author presents its characteristic features and various types of such spaces with differing tourism landscapes. The landscapes of tourism space are treated not only as tourism assets or attractions, but also as the consequences of tourism activity on the natural and cultural environment.